2007
DOI: 10.4141/a06-028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mechanical processing of corn silage on in vitro ruminal fermentation, and in situ bacterial colonization and dry matter degradation

Abstract: . Effect of mechanical processing of corn silage on in vitro ruminal fermentation, and in situ bacterial colonization and dry matter degradation. Can. J. Anim. Sci. 87: 259-267. Rumen fermentation and bacterial colonization of mechanically processed corn silage were evaluated in a series of in vitro and in situ experiments using ruminally cannulated cows. Data from rumen-simulated continuous culture (Rusitec) showed that total VFA concentration was increased (P < 0.001) by feeding processed corn silage, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…The higher amount of starch present in MS has been associated with increased relative abundances of members of the families Ruminococcaceae and Succinivibrionaceae [40,41], which is consistent with the positive association of UCG-002, Succinivibrio and UCG-014 with the GS0 fed cows in the present study. Low CH 4 producing cows have been positively associated with lactate and succinate producing bacteria [42].…”
Section: Effect Of Diet and Time On Rumen Bacterial Compositionsupporting
confidence: 90%
“…The higher amount of starch present in MS has been associated with increased relative abundances of members of the families Ruminococcaceae and Succinivibrionaceae [40,41], which is consistent with the positive association of UCG-002, Succinivibrio and UCG-014 with the GS0 fed cows in the present study. Low CH 4 producing cows have been positively associated with lactate and succinate producing bacteria [42].…”
Section: Effect Of Diet and Time On Rumen Bacterial Compositionsupporting
confidence: 90%
“…The higher amount of starch present in MS has been associated with increased relative abundances of members of the families Ruminococcaceae and Succinivibrionaceae (Kozakai et al, 2007;Deusch et al, 2017), which is consistent with the positive association of UCG-002, Succinivibrio and UCG-014 with the GS0 fed cows in the present study. Low CH4 producing cows have been positively associated with lactate and succinate producing bacteria (Danielsson et al, 2017).…”
Section: Effect Of Diet and Time On Rumen Bacterial Compositionsupporting
confidence: 90%
“…Andrae et al (2001) reported that MP with a roll clearance of 1 mm increased total tract starch digestibility by 5%, which was similar to that observed in our trial. Kozakai et al (2007) indicated that MP of corn kernels resulted in quicker bacterial attachment after feeding, possibly due to increased damage on the surface area of the plant material. Intact corn kernels present in the CS tended to be lower as the roll clearance decreased from 5 mm to 1 mm .…”
Section: Apparent Ruminal and Total Tract Digestibilitymentioning
confidence: 99%